Exploring quality challenges and the validity of excellence models. Issue 10 (3rd October 2016) - Eriksson, Henrik; Gremyr, Ida; Bergquist, Bjarne; Garvare, Rickard; Fundin, Anders; Wiklund, Håkan; Wester, Michael; Sörqvist, Lars
Abstract : Purpose: The purpose of this paper is to identify and explore important quality-related challenges facing organizations, and investigate how current excellence models incorporate these challenges. Design/methodology/approach: The paper is based on a Delphi study of Swedish organizations. Forty-nine challenges were generated and ranked according to importance and the ten top-ranked challenges were compared to the principles of four excellence models. Findings: The excellence models still seem to be relevant since their content matches many of the identified challenges. The Malcolm Baldrige National Quality Award and the Swedish Institute for Quality models were found to have the most comprehensive coverage, while the International Organization for Standardization model had limited coverage. Research limitations/implications: Three areas for further research were identified: first, how quality management (QM) can evolve in different contexts that have varying needs in terms of adaptive and explorative capabilities; second, the interfaces of QM and sustainability, and ways to understand how customers and stakeholders can be active contributors to improvements; and third, the roles of the owners and board of directors regarding QM, and how to organize and distribute responsibilities of the QM work. Practical implications: There are three important challenges that future revisions of excellence models could address: first, making QM a strategic issue for company owners; second, involving customers in the improvement activities; and third, developing processes that are robust yet still easily adaptable. Originality/value: The Delphi study identified upcoming challenges in the QM area based on input from 188 quality professionals.